Intergeneration Dynamics and Knowledge Sharing in Family Business Sustainability - Idris, Idris; Hersugondo, Hersugondo; Mahfud, Mahfud; Sugeng, Wahyudi; Muhammad, Nasir; Tumpal, Situmorang (Journal of Ecohumanism, 2025)
Family business sustainability relies heavily on the interplay of intergenerational dynamics, where the effective transfer of knowledge, values, and relational resources is pivotal. This study explores the role of entrepreneurial knowledge sharing in enhancing intergenerational relationship quality and its subsequent impact on the sustainability of family businesses. Using the Resource-Based View (RBV) as a theoretical foundation, this research investigates how relational resources contribute to competitive advantage in the unique socio-cultural context of Central Java, Indonesia. The study employs Structural Equation Modeling (SEM) to analyze data collected from 200 family business owners through purposive sampling. The results demonstrate that entrepreneurial knowledge sharing significantly improves intergenerational relationship quality (β = 0.78, p = 0.012), which, in turn, has a strong positive effect on family business sustainability (β = 0.84, p = 0.007). Furthermore, intergenerational relationship quality acts as a partial mediator (β = 0.35, p = 0.009), amplifying the impact of knowledge sharing on sustainability. The findings highlight the dual role of entrepreneurial knowledge sharing in fostering both relational harmony and business performance. This research contributes to the literature by integrating cultural insights into the RBV framework and offering actionable strategies for family businesses to sustain their legacy. By institutionalizing trust, shared vision, and effective communication practices, family businesses can bridge generational divides and maintain competitiveness in dynamic market environments.